Toward unitary taxation of MNEs - Sol Picciotto (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
Protracted debates and negotiations have led to a new approach to taxation of multinationals: apportionment of their global profits based on their real presence in each country. A concerted initiative by willing states could implement this approach using standards now agreed, facilitated through the UN Framework Convention now under negotiation.
Keywords: 330